To teach : the journey, in comics - Ayers, William, 1944-; Alexander-Tanner, Ryan. (New York : Teachers College Press, 2010)
'This graphic novel brings to life William Ayers's bestselling memoir To teach : the journey of a teacher, third edition. From Ayers's early days teaching kindergarten, readers follow this renowned educational theorist on his'voyage of discovery and surprise.''--Cover, p. [4].
Introduction : welcome to our comic book -- Opening day : the journey begins -- Seeing the student -- Creating an environment for learning -- Building bridges -- Liberating the curriculum -- Keeping track -- The mystery of teaching -- Commencement : beginning again -- Further readings.
Includes bibliographical references.
Keywords: Teaching -- Comic books, strips, etc; Teachers -- Comic books, strips, etc